APPLICATION OF SOLID DISPERSION TECHNIQUE IN SOLUBILITY AND DISSOLUTION RATE ENHANCEMENT OF NATEGLINIDE - Boddu, Prasanthi; Cherakapu, Venkata Lakshmi; Ponukumati, Uma Devi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Nateglinide (NTG) is a potent short-acting biopharmaceutical classification system class II antidiabetic medication. The primary objective of the present investigation was to prepare and evaluate solid dispersions of NTG to enhance the component solubility and immediate release (IR) profile. The secondary objective was to formulate sustained release (SR) matrix layer of NTG for prolonging its effect in the body and to decrease oscillations in plasma concentration level. Methods: NTG (270 mg) SR layer was formulated using release retardant polymers such as Carbopol, ethyl cellulose (EC), hydroxy EC, hydroxypropyl methylcellulose (HPMC), Kollidon, and locust bean gum at concentrations of 15% and 30%. IR layer of NTG (60 mg) was formulated using drug: Polymer inclusion complexes (1:1 and 1:2) of β-cyclodextrin (CD), HP β-CD, polyvinylpyrrolidone (PVP) K-15, and PVP K-30 by physical mixing and kneading methods (KMs). Results: Among the all the carriers tested HP β-CD at 1:2 ratio prepared by KM (I3) gave highest enhancement of dissolution rate and dissolution efficiency with acceptable f1 (10.5) and f2 (51.0) values in comparison to marketed IR tablets (Starlix-60®). The SR formulation S12 was able to show a minimum amount of drug release (15%) within 1 hr comparatively, with a complete and sustained effect on drug release. Conclusion: Thus, HPMC K-100M at a concentration of 30% in the SR layer in combination with HP β-CD (1:2) solid dispersions in the IR layer may be used in the design of oral controlled drug delivery system for NTG.